PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, PROPORSI DEWAN KOMISARIS INDEPENDEN, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP TAX AVOIDANCE - Ghea Prameswara Hapsari; Triyono Triyono (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine how the influence given by the profitability, firm size, the proportion of independent commissioners, and the proportion of institutional ownership on tax avoidance. The sample in this study are manufacturing companies that listing on the Indonesia Stock Exchange from 2016 to 2020. The sampling technique was carried out using the purposive sampling method by applying certain criteria to obtain 80 samples consisting of 16 companies. The method used in this research is quantitative method with classical assumption test and multiple linear regression test. The results show that the company's performance as measured by ROA has an effect on Tax Avoidance by the company. In addition, the proportion of institutional ownership also affects Tax Avoidance activities. However, the results of the study indicate that the variables of firm size and the proportion of independent commissioners have no effect on tax avoidance